Analytical Modeling and Numerical Simulation of Nonlinear Thermal Effects in Bipolar Transistors - D'Alessandro, Vincenzo; Scognamillo, Ciro; Catalano, Antonio Pio; Muller, Markus; Schroter, Michael; Zampardi, Peter J.; Codecasa, Lorenzo (Collection of papers presented at the ... International Workshop on Thermal Investigations of ICs and Systems, 2022)
This paper addresses the problem of modeling nonlinear thermal effects in bipolar transistors under static conditions. The impact of these effects on the thermal resistance is explained in detail and analytically modeled using the assumption of a single-semiconductor device. FEM thermal simulations of high-frequency transistors are performed to evaluate the accuracy of the single-semiconductor theory and of the thermal resistance formulations currently employed in the most popular compact transistor models. It is shown that these models do not correctly account for nonlinear thermal effects. Various implementations of the more accurate single-semiconductor theory are then suggested for their future releases.